Chromosome 9 Inversion: Pathogenic or Benign? A Comprehensive Systematic Review of all Clinical Reports - Mohsen-Pour, Neda; Talebi, Taravat; Naderi, Niloofar; Moghadam, Maryam H.; Maleki, Majid; Kalayinia, Samira (Current Molecular Medicine, 2022)
Background: Inversion of chromosome 9 (inv[9]) is known as one of the most common structural balanced chromosomal variations. Chromosome 9 is highly susceptible to structural rearrangements, specifically to pericentric inversions. Various investigators have posited that inv(9) with different breakpoints could be the cause of several abnormal conditions in individuals, whereas others have considered it a benign variant. To our knowledge, a consensus regarding the effects of this inversion has yet to emerge. Objective: This study aims to discuss the pathogenic/benign effects of inv(9) in all possible clinical conditions detected in the occurrence of this abnormality. Methods: Studies on inv(9) were collected via PubMed, MalaCards, Google Scholar, and NORD, along with the search terms of inv(9), pericentric inv(9), and chromosome 9 variants. Additionally, the incidence of inv(9) and the karyotype and clinical findings of individuals reported with this variant were investigated. Results: The collection of the studies reviewed shows that inv(9) is associated with various conditions such as congenital anomalies, growth retardation, infertility, recurrent pregnancy loss, and cancer. The clinical features associated with this variant in humans vary between growth stages. Further, there have been no shared clinical findings in a specific period. Conclusion: Although there is no conclusive evidence for the pathogenicity of this rearrangement, prenatal genetic counseling on inv(9) and further clinical and molecular studies would be helpful in chromosome 9-related problems.
Keywords: Clinical findings